Análise da assembleia fitolítica do solo aplicada no holoceno médio: caso da Estação Ecológica da Mata Preta - Abelardo Luz (SC) - Ewald, Paula Louíse de Lima Felipe (2015)
In the Quaternary period, the south of Brazil has suffered from paleoclimate instabilities which have generated changes in the landscape. Pedological, sedimentological and paleoenvironmental reconstructions studies have been developed by the group Gênese e Evolução de Superfícies Geomórficas e Formações Superficiais - UNIOESTE-FB to investigate the paleoclimate influence on the landscape setting of the Southwest region in Paraná and Northwest region in Santa Catarina States. Aiming to contribute with these studies, this research has sought to investigate the evolution of the vegetation at Ecological Station Mata Preta in Abelardo Luz (Santa Catarina State) and to verify the hypothesis of occurrence of vegetation changes over the Holocene in the studied area. Specifically, the goal was to determine the phytolith signature of the current vegetation and to assess its variability in the superficial soil horizons under the Mixed Ombrophylous Forest (FOM - Araucaria Forest) and to know the historical trajectory of the changes in the vegetation of the area of study during the Holocene Era. Routine physical and chemical analyses have been used to characterize a soil profile and phytolith and isotopic analyses (δ13C of the soil organic matter - SOM and datation14Cof humin fraction) in a soil profile (Profile 1) and more three Control Points (PC1, PC2 and PC3). The physical and chemical analyses of the soil allowed the classification of the studied soil as a Humic Dystrophic Inceptisol. The values of δ13C of the SOMpointed to a vegetation change between the Middle Holecene and the Late and the phytolith assembly of the soil allowed the refining of this interpretation. Thus, it is possible to infer that his soil registers a period during which the vegetation was formed by a prevailing community of C4plants (more open than the current one), in the Middle/Early Holocene (6.235-6.215 years Cal. AP), evolving to a mixed vegetation, more forested and similar to the current one, composed, predominantly, of C3plants, in the Late Holocene (from 840 to 835 years cal. A.P.) which evolved to the current FOM. Based on the litterphytolith assemblage and on the superficial layers of the Inceptisol and the PC´s, it has been defined the phytolith signature of the FOM, which is formed by 14 morphotypes of phytoliths which represent the families of Poaceae (subfamilies Panicoid; Pooid; Chloridoid and Bambusoid), Eudicotiledoneae, Arecaceae and Cyperaceae.